Consensus Document ANMCO/ANCE/ARCA/GICR-IACPR/GISE/SICOA: Long-term Antiplatelet Therapy in Patients with Coronary Artery Disease. (31st May 2018) - Gulizia, Michele Massimo; Colivicchi, Furio; Abrignani, Maurizio Giuseppe; Ambrosetti, Marco; Aspromonte, Nadia; Barile, Gabriella; Caporale, Roberto; Casolo, Giancarlo; Chiuini, Emilia; Di Lenarda, Andrea; Faggiano, Pompilio; Gabrielli, Domenico; et al.
Abstract: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor inhibitor is the cornerstone of pharmacologic management of patients with acute coronary syndrome (ACS) and/or those receiving coronary stents. Long-term (>1 year) DAPT may further reduce the risk of stent thrombosis after a percutaneous coronary intervention (PCI) and may decrease the occurrence of non-stent-related ischaemic events in patients with ACS. Nevertheless, compared with aspirin alone, extended use of aspirin plus a P2Y12 receptor inhibitor may increase the risk of bleeding events that have been strongly linked to adverse outcomes including recurrent ischaemia, repeat hospitalisation and death. In the past years, multiple randomised trials have been published comparing the duration of DAPT after PCI and in ACS patients, investigating either a shorter or prolonged DAPT regimen. Although the current European Society of Cardiology guidelines provide a backup to individualised treatment, it appears to be difficult to identify the ideal patient profile which could safely reduce or prolong the DAPT duration in daily clinical practice. The aim of this consensus document is to review contemporary literature on optimal DAPT duration, and to guide clinicians in tailoring antiplatelet strategies in patients undergoing PCI or presenting with ACS.